1990
DOI: 10.3109/10731199009117327
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion to the Surfaces of Polymeric Beads

Abstract: The main goal of this study is to determine the relationship between the surface properties of polymeric materials and fibroblastic cell adhesion. Therefore, two series of polymeric beads, PHEMA and PS, were tested in microcarrier-facilitated cell culture systems. The crosslinked PHEMA beads were prepared by suspension polymerization of HEMA monomer in the presence of various acrylic monomers (i.e. MMA, EGDMA, DMAEMA). The hydrophobic PS beads were used after coated with different alkylamine monomers (i.e. EDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…This result is in agreement with a study re-620 ported by Yan and co-workers[19]. First, the interaction between 621 carboxyl and amino groups on PLGA and chitosan, respectively, 622 provided the resultant PEC microcarriers with a suitable weakly 623 positively charged surface for attached cell growth[44,45]. Second, 624 the presence of PLGA increased the hydrophilicity of the PEC 625 microspheres, due to the higher hydrophilicity and greater water 626 absorption capability of the residual -COOH groups in PLGA than 627 those of the residual -NH 2 groups in chitosan in the PEC porous 628 microcarriers, thus improving cell attachment and proliferation…”
supporting
confidence: 91%
“…This result is in agreement with a study re-620 ported by Yan and co-workers[19]. First, the interaction between 621 carboxyl and amino groups on PLGA and chitosan, respectively, 622 provided the resultant PEC microcarriers with a suitable weakly 623 positively charged surface for attached cell growth[44,45]. Second, 624 the presence of PLGA increased the hydrophilicity of the PEC 625 microspheres, due to the higher hydrophilicity and greater water 626 absorption capability of the residual -COOH groups in PLGA than 627 those of the residual -NH 2 groups in chitosan in the PEC porous 628 microcarriers, thus improving cell attachment and proliferation…”
supporting
confidence: 91%
“…The use of microcarrier concentration over 1 g/L was found to result in loss of inoculum, poor growth, and cell detachment (van Wezel, 1977). Kiremitci and Piskin (1990) also reported that the microcarriers significantly inhibited the cell culture when used in large amounts. The optimal charge density varies according to different matrix materials and charge groups.…”
Section: Effect Of Surface Charge and Charge Density Of Microcarriersmentioning
confidence: 95%
“…In our initial experiments, we found that the yield of DCs per unit of culture surface area in closed gas‐permeable cell culture bags was less than that in the open‐flask systems. In an effort to improve the yields of DCs in the closed system, we introduced styrene copolymer beads (90‐ to 125‐μ diameter; density, 1.05 g/cm 3 ; SoloHill Engineering, Ann Arbor, MI) into the bags to increase the available surface area (by 380 cm 2 ) and to supply a surface area similar to that found in the flasks 5 . In a biologic safety cabinet, 1 g of gamma‐radiation‐sterilized beads and 10 × 10 8 total cells per bag from the MNC product were diluted in 100 mL of medium (AIM‐V, GIBCO, Grand Island, New York) and loaded into gas‐permeable cell culture bags (Lifecell X‐fold Cell Culture Container PL2417, 180 cm 2 , Nexell Therapeutics, Irvine, CA).…”
Section: Comparison Of DC Culture Methodsmentioning
confidence: 99%